Taxonomic and Enzymatic Characterization of Flocculibacter collagenilyticus gen. nov., sp. nov., a Novel Gammaproteobacterium With High Collagenase Production - Li, Jian; Cheng, Jun-Hui; Teng, Zhao-Jie; Sun, Zhong-Zhi; He, Xiao-Yan; Wang, Peng; Shi, Mei; Song, Xiao-Yan; Chen, Xiu-Lan; Zhang, Yu-Zhong; Tian, Xinmin; Zhang, Xi-Ying (Frontiers in Microbiology, 2021)
Collagens from marine animals are an important component of marine organic nitrogen. Collagenase-producing bacteria and their collagenases play important roles in collagen degradation and organic nitrogen recycling in the ocean. However, only a few collagenase-producing marine bacteria have been so far discovered. Here, we reported the isolation and characterization of a collagenase-secreting bacterium, designated strain SM1988T, isolated from the surface of a green alga Codium fragile sample. Strain SM1988T is a Gram-negative, aerobic, oxidase- and catalase-positive, unipolar flagellated, and rod-shaped bacterium capable of hydrolyzing casein, gelatin and collagens. Phylogenetic analysis revealed that strain SM1988T formed a distinct phylogenetic lineage along with known genera within the family Pseudoalteromonadaceae, with sequence similarity being less than 93.3% to all known species in the family. Based on the phylogenetic, genomic, chemotaxonomic and phenotypic data, strain SM1988T was considered to represent a novel species in a novel genus in the family Pseudoalteromonadaceae, for which the name Flocculibacter collagenilyticus gen. nov., sp. nov. is proposed, with the type strain being SM1988T (= MCCC 1K04279T = KCTC 72761T). Strain SM1988T showed a high production (236 U/mL) of extracellular collagenases, which had high activity against both bovine collagen and codfish collagen. Biochemical tests combined with genomic and secretomic analyses indicated that the collagenases secreted by strain SM1988T are serine proteases from the S8 family. These data suggest that strain SM1988T acts as an important player in marine collagen degradation and recycling and may have a promising potential in collagen resource utilization.